2013
DOI: 10.1136/annrheumdis-2013-eular.1575
|View full text |Cite
|
Sign up to set email alerts
|

FRI0448 Radiological occult sacroiliac abnormalities in asymptomatic patients with inflammatory bowel disease (IBD) might precede the development of spondyloartropathy

Abstract: Background The involvement of sacroiliac joints (SIJ) is one of the major features of Spondyloartropathies (SpA) associated to inflammatory bowel disease (IBD) and it is well known that the early detection of SIJ inflammation is crucial to identify and treat SpA on-time. Objectives To investigate X rays sacroiliitis in IBD patients, not presenting signs and symptoms of Spondyloarthropathy (SpA), and the differences of IBD clinical and familial variables between patients with sacroiliac (SIJ) abnormalities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This unusually wide margin likely stems from heterogeneity of study population across studies, differences in methodology and definitions of sacroiliitis, that is, modified New York (mNY) criteria or MRI-based definitions [9]. Prospectively enrolled IBD patients without any back pain were noted to have occult sacroiliitis in 24-27.1% on radiographs [10,11]; however, it is unclear whether these radiographs met mNY criteria. On follow-up studies, these IBD cohorts showed an association of occult sacroiliitis with peripheral arthritis and erythema nodosum and 18% developed back pain, and hence ax-SpA diagnosis in 3 years [10,11].…”
Section: Prevalence Of Inflammatory Bowel Disease Associated Sacroili...mentioning
confidence: 99%
See 1 more Smart Citation
“…This unusually wide margin likely stems from heterogeneity of study population across studies, differences in methodology and definitions of sacroiliitis, that is, modified New York (mNY) criteria or MRI-based definitions [9]. Prospectively enrolled IBD patients without any back pain were noted to have occult sacroiliitis in 24-27.1% on radiographs [10,11]; however, it is unclear whether these radiographs met mNY criteria. On follow-up studies, these IBD cohorts showed an association of occult sacroiliitis with peripheral arthritis and erythema nodosum and 18% developed back pain, and hence ax-SpA diagnosis in 3 years [10,11].…”
Section: Prevalence Of Inflammatory Bowel Disease Associated Sacroili...mentioning
confidence: 99%
“…Prospectively enrolled IBD patients without any back pain were noted to have occult sacroiliitis in 24-27.1% on radiographs [10,11]; however, it is unclear whether these radiographs met mNY criteria. On follow-up studies, these IBD cohorts showed an association of occult sacroiliitis with peripheral arthritis and erythema nodosum and 18% developed back pain, and hence ax-SpA diagnosis in 3 years [10,11]. McEniff et al [12] showed prevalence of sacroiliitis meeting mNY criteria was slightly higher (32%) when computed tomography (CT) was utilized.…”
Section: Prevalence Of Inflammatory Bowel Disease Associated Sacroili...mentioning
confidence: 99%
“…After the introduction of the Assessment of Spondyloarthritis International Society (ASAS) classification criteria in 2009 [15], the use of sacroiliac magnetic resonance for early findings of pre-radiographic axial spondyloarthritis (ax-SpA) decreased the DD and the incidence of bamboo spine, thanks to quicker access to treatments [11,[16][17][18][19][20][21].…”
Section: Of 20mentioning
confidence: 99%